In Defence of Reconciliation. Issue 1 (January 2014) - Freeman, Victoria
Abstract : Indigenous scholars and others have characterized Canadian discourses of reconciliation as supporting a top-down, government-defined and controlled agenda, which is at best ineffective and misleading and at worst fraudulent and recolonizing. Some have argued that reconciliation should only occur after the Indian Act has been abolished, reparations made, land and resources returned, and a political and economic nation-to-nation relationship restored. The author agrees that it is essential to look critically at state and nationalistic discourses of reconciliation and that neither the federal government, the churches, nor non-Indigenous peoples generally can or should control the agenda. However, while reconciliation is not a sufficient condition for decolonization in Canada, Indigenous resurgence on its own will not achieve full decolonization either. If the psychic structures of colonialism persist, various forms of neocolonialism will be prevalent even after a nominal "nation-to-nation" relationship has been established, given the demographic imbalance and geographical proximity between Indigenous and non-Indigenous peoples. There will always be a need for relationship and negotiation. In fact, decolonization and reconciliation may be understood as complementary and concurrent processes. The concept of reconciliation underlines the emotional, psychological and human changes that are as necessary as political and economic reformulations for decolonization and that are not easily addressed by other means. Rather than a top-down government-initiated campaign focused on assimilation into the status quo or a Eurocentric Christian doctrine focused on forgiveness, reconciliation can be a transformative process of building the relationships, alliances and social understandings necessary to support the systemic changes that true decolonization entails. Indigenous and other cultural paradigms for resolving conflicts, making restitution and healing relationships, such as the Sto:lo concept of lummi or "facing yourself, " can help restore interconnectedness and reciprocity at all levels, both within Indigenous communities and between Indigenous and non-Indigenous peoples and the land. We also should not overestimate the government's power to control even those reconciliation processes it does initiate, let alone those that arise autonomously. Decolonization and reconciliation are processes underway on many fronts in Canada, and they can't be controlled by anyone.